Glycemic Index Values Of Instant Multigrain Beverage: Current Knowledge And Future Prospects - Zikri, Wan Zulaikha Adrina Wan Ahmad (Universiti Sains Malaysia, 2020)
Grains often consumed as food but with advanced technology, it is in powdered form which is convenient to consumers as they can prepare it instantly. Instant multigrain beverage product provides longer shelf life and convenient to sedentary people. The study is aimed to study the glycemic index values for instant multigrain beverage based on current knowledge and future prospects, observe the differences between methods based on in vitro and clinical trial method for determination of glycemic index and to suggest the recommended glycemic index values for instant multigrain beverage based on previous studies. From the results, the strength of the current study on clinical trial is greater than in vitro method because of its accuracy. However, previous studies shown that in vitro method have fewer limitations compared to clinical trial that were described as costly, time-consuming, laborious and required participants among human beings that are motivated to complete the study research. And it can be concluded that instant multigrain beverage is considered having low GI value based on several previous studies done by researchers worldwide. Most multigrain products evaluated as low GI due to their high dietary fibre content, high protein content and other studies that resulted in slow glycemic response when consuming multigrain products. The recommended glycemic value between 30-40, averaged as 35.